Psychometric Properties of the Revised and Abbreviated form of the Turkish Version of the Dysfunctional Attitude Scale. Issue 1 (February 2016) - Batmaz, Sedat; Ozdel, Kadir
Dysfunctional attitudes are considered to be important risk factors in the onset and maintenance of depression. Thus, a psychometrically reliable and valid measure is necessary for understanding depression. The Dysfunctional Attitude Scale (DAS) is widely used and has good psychometric properties, but there is no consensus about its factor structure. To examine its psychometric properties and factor structure, a total of 885 individuals consisting of patients with depression and healthy controls were evaluated. After the sample was randomly divided into two subsets, exploratory and confirmatory factor analyses were performed. Then the DAS was abbreviated according to the factor profiles and theoretical background. Analyses indicated two factors, named Perfectionism/Achievement and Need for Approval/Dependency for the revised DAS . Reliability analyses revealed a good internal consistency, and the concurrent validity indicated significant correlations with the Beck Depression Inventory and the Automatic Thoughts Questionnaire.